OPTIMASI PEMBUATAN PRODUK YOGHURT MEREK MILKYLAND DI KOTA DEPOK, PROVINSI JAWA BARAT - Rachim, Faiza (Universitas Muhammadiyah Palembang, 2021)
Milk is one of the intakes produced from the liquid milk of cows, buffaloes, horses, goats, sheep, and other dairy-producing livestock, both fresh and heated through pasteurization, Ultra High Temperature (UHT) or sterilization processes. Fresh milk is a highly nutritious beverage ingredient because it contains complete and balanced beverage substances such as protein, fat, carbohydrates, minerals, and vitamins that are needed by humans. This research combines several methods, such as hedonic analysis to determine the level of product acceptance for customers, proximate analysis to determine the nutritional content of products, and business business plans to determine business viability and business prospects for further expansion. The results showed that the products sold by Milkyland were accepted by customers and the nutrition of the product could also replace or replace one meal from three meals per day based on the 2013 AKG.